2006
DOI: 10.1128/jvi.00152-06
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection Is Not Associated with Small Intestinal Fluid Secretion in the Adult Mouse

Abstract: In contrast to humans, adult but not infant small animals are resistant to rotavirus diarrhea. The pathophysiological mechanism behind this age-restricted diarrhea is currently unresolved, and this question was investigated by studying the secretory state of the small intestines of adult mice infected with rotavirus. Immunohistochemistry and histological examinations revealed that rotavirus (strain EDIM) infects all parts of the small intestines of adult mice, with significant numbers of infected cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…2A and B). This conclusion is further supported by our observation that even adult mice have similar pathological lesions at the same time points but no diarrhea (28). Apparently, RV-induced pathological lesions per se in the small intestine (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…2A and B). This conclusion is further supported by our observation that even adult mice have similar pathological lesions at the same time points but no diarrhea (28). Apparently, RV-induced pathological lesions per se in the small intestine (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have shown that the small intestine of infant mice (11,35) but not adult mice (28) respond with electrolyte and water secretion (diarrhea) following infection with murine RV. In diarrhea-resistant adult mice there was a most modest increase of intestinal motility at 24 h p.i.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The myenteric plexus provides motor innervation to the circular muscle layer and the longitudinal muscle and regulates intestinal motility including peristalsis 142 . Over the years, it has become more and more evident that ENS is involved in rotavirus diarrhea 30,[74][75][76][77] . By blocking enteric neurotransmitters, that can act to induce active secretion (e.g.…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%